The relationship between economic growth, budget balance, tax revenue and government debt - Abkenar, Seyedeh Fatemeh Alavi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
ABSTRACT: The main focus of this thesis is to investigate the impact some selected macroeconomic variables such as gross capital formation, inflation, trade openness, budget balance, central government debt and tax revenue on growth percentage of GDP of four selected countries from South America, North America and Middle East for the period of 1995-2010. In this study first we examined the relationship and impact of gross capital formation, inflation, trade openness together with budget balance on growth percentage of GDP. Second stage was examining the impact of gross capital formation; inflation and trade openness together with tax revenue on growth percentage of GDP of each country and last part of individual country regression belong to investigating the impact of gross capital formation, inflation, trade openness and stock of public debt on economic growth of each country separately. Afterward we employed panel data, pooled white cross-section time series to investigate the long run impact of relationship examined separately for our countries as a group. Result of our work indicates there’s positive correlation between gross capital formation and growth percentage of GDP. The same result has been proofed for nexus between budget balance and growth percentage of GDP. Keywords: Macroeconomic Variables, Growth Percentage of GDP, South America, North America, Middle East. ………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Bu tez, Guney Amerika, Kuzey Amerika ve Ortadogu ulkelerinin 1995-2000 yillari arasindaki enflasyonun, ticari serbestliginin,butce dengesinin,gayri safi sermaye olusumunun, devlet borcunun ve vergi gelirlerinin buyumeye etkisini arastirmayi amaclamaktadir. Bu arastirmada oncelikle gayri safi sermaye olusumunun, enflasyonun ve ticari serbestligin gayri safi milli hasiladaki buyumeye etkisini inceledik. Ikinci asamada ise enflasyonun, ticari serbestligin, butce dengesinin, gayri safi sermaye olusumunun, devlet borcunun ve vergi gelirlerinin her ulke icin ayri ayri olmak kosuluyla, gayri safi milli hasilanin buyumeye etkisini inceledik. Son kisimda ise bu etkenlerin ve devlet borcunun bu ulkelerdeki iktisadi buyumeye olan etkilerini arastirdik. Daha sonra capraz kesitli frekans dagilimli inceleme methodu ile ulkeleri grup halinde inceleyerek, uzun vadedeki etkilerini arastirdik.Incelemelerimizin ve analizlerimizin sonucunda gayri safi sermaye olusumu ile gayri safi milli hasiladaki yillik buyumede pozitif bir korelasyon oldugunu gorduk. Ayni bagin butce dengesi ve gayri safi mili hasila arasinda da oldugunu ispatlamis olduk. Ancak,ticari serbestligin, enflasyonun devlet borcunun ve vergi gelirlerinin buyume icin pozitif degil, aksine negative bir yansima yaptigini da ispatlamis olduk. Anahtar Kelimeler: makroekonomik degiskenler, gayri safi milli hasila buyumesi, guney amerika, kuzey amerika, ortadogu.
Master of Business Administration. Thesis (M.B.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2013. Supervisor: Prof. Dr. Serhan Çiftçioğlu.
Keywords: Business Administration; Macroeconomic Policy - Economic Conditions and Development - South America - North America - Middle East; Macroeconomic Variables, Growth Percentage of GDP, South America, North America, Middle East